IMPOLITENESS STRATEGIES REFLECTED IN GORDON RAMSAY'S IN “HELLS KITCHEN SEASON 10”: PRAGMATICS APPROACH - Sonia Rahman; Zia Hisni Mubarak (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
. The purpose of this study was to identify the strategies of impoliteness used in conversation. This impoliteness strategies were used by the person who appeared in the reality television show entitled Hell's Kitchen. The data was taken from the Hell's Kitchen video and directly translated based on the video narration. The data analysis focused on the person from the scene in the perception video. This research was written and then examined based on the considerations put forward by Culpeper (1996) Culpeper (1996). The researcher found that there were only three impoliteness of strategy were included in the category of 7 Bald on record Impoliteness, 2 Negative Impoliteness, and 6 Sarcasm, or Mock Impoliteness conducted by Gordon Ramsay to reality show participants Hell's Kitchen television. This research was a qualitative research, will be used to analyze the types and strategies Impoliteness therefore theory Culpeper (1996) will be used to analyze the explanation of the Impoliteness.